The Association and Pathogenesis of SERPINA3 in Coronary Artery Disease - Li, Bo; Lei, Zhijun; Wu, You; Li, Bingyu; Zhai, Ming; Zhong, Yuan; Ju, Peinan; Kou, Wenxin; Shi, Yefei; Zhang, Xianling; Peng, Wenhui (Frontiers in Cardiovascular Medicine, 2021)
Background: Serine proteinase inhibitor A3 (SERPINA3) has been discovered in the pathogenesis of many human diseases, but little is known about the role of SERPINA3 in coronary artery disease (CAD). Therefore, we aim to determine its relationship with CAD and its function in the pathogenesis of atherosclerosis. Methods: In total 86 patients with CAD and 64 patients with non-CAD were compared. The plasma SERPINA3 levels were measured using ELISA. Logistic regression analysis and receiver-operating characteristic (ROC) analysis were performed to illustrate the association between plasma SERPINA3 levels and CAD. In vitro, real-time PCR (RT-PCR) and immunofluorescence staining were used to determine the expression of SERPINA3 in atherosclerotic plaques and their component cells. Then rat aortic smooth muscle cells (RASMCs) were transfected with siRNA to knock down the expression of SERPINA3 and human umbilical vein endothelial cells (HUVECs) were stimulated by SERPINA3 protein. EdU assay and scratch assay were used for assessing the capability of proliferation and migration. The cell signaling pathway was evaluated by western blot and RT-PCR. Results: Patients with CAD [104.4(54.5–259.2) μg/mL] had higher levels of plasma SERPINA3 than non-CAD [65.3(47.5–137.3) μg/mL] (P = 0.004). After being fully adjusted, both log-transformed and tertiles of plasma SERPINA3 levels were significantly associated with CAD. While its diagnostic value was relatively low since the area under the ROC curve was 0.64 (95% CI: 0.55–0.73). Secreted SERPINA3 might increase the expression of inflammatory factors in HUVECs. Vascular smooth muscle cells had the highest SERPINA3 expression among the aorta compared to endothelial cells and inflammatory cells. The knockdown of SERPINA3 in RASMCs attenuated its proliferation and migration. The phosphorylated IκBα and its downstream pathway were inhibited when SERPINA3 was knocked down. Conclusions: Elevated plasma SERPINA3 levels were associated with CAD. SERPINA3 can increase inflammatory factors expression in HUVECs. It can regulate VSMCs proliferation, migration, and releasing of inflammatory factors through the NF-κB signaling pathway. Thus, SERPINA3 played a significant role in the pathogenesis of atherosclerosis.